2018
DOI: 10.1007/978-3-662-58485-9_10
|View full text |Cite
|
Sign up to set email alerts
|

A Process Model for Enhancing Digital Assistance in Knowledge-Based Maintenance

Abstract: Digital transformation and evolution of integrated computational and visualisation technologies lead to new opportunities for reinforcing knowledge-based maintenance through collection, processing and provision of actionable information and recommendations for maintenance operators. Providing actionable information regarding both corrective and preventive maintenance activities at the right time may lead to reduce human failure and improve overall efficiency within maintenance processes. Selecting appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Hence, the authors have made efforts persistently to extend the definition of KBM particularly from the perspective of semantic modelling and representation as well as static rule-based or dynamic modelbased analytics (e.g. in Ansari 2014, Matyas et al 2017, Ansari, Glawar, and Sihn 2017, Kovacs et al 2019. From the perspective of knowledge management (c.f.…”
Section: ✓ ✓mentioning
confidence: 99%
“…Hence, the authors have made efforts persistently to extend the definition of KBM particularly from the perspective of semantic modelling and representation as well as static rule-based or dynamic modelbased analytics (e.g. in Ansari 2014, Matyas et al 2017, Ansari, Glawar, and Sihn 2017, Kovacs et al 2019. From the perspective of knowledge management (c.f.…”
Section: ✓ ✓mentioning
confidence: 99%
“…First, a literature review was made to identify, which technical configuration options for assembly assistance systems were the most relevant. Taxonomies define different aspects as by Hinrichsen et al (2016), Lusic et al (2016), Kovacs et. al (2018) and Keller et al (2019) were identified.…”
Section: Methodsmentioning
confidence: 99%